Analisis Komparasi Prinsip, Sistem dan Prosedur Penyaluran Dana untuk Usaha Mikro secara Konvensional dan Syariah: (Studi Multi Kasus Pada PT Bank Mandiri (Persero) Tbk dan PT Bank Syariah Mandiri Cabang Samarinda) - E. Retno Maninggarjati; Ratna Wulaningrum; Evi Dwi Rachmawati; Ita Aprillia (Politeknik Negeri Samarinda, 2022)
The purpose of this research is to find out the comparison of channeling funds for micro businesses between conventional banks and Islamic banks, then to find out the implementation according to the Financial Services Authority Regulation Number 42 / POJK.03 / 2017 at PT Bank Mandiri (Persero) Tbk and PT Bank Syariah Mandiri. Problem solving uses a method that is done by combining observations, interviews, documentation and regulations of the Act. The results of this study indicate that the implementation of channeling Credit or Micro Business Financing funds at PT Bank Mandiri (Persero) Tbk and PT Bank Syariah Mandiri Samarinda Branch is in accordance with the Financial Services Authority Regulation Number 42 / POJK.03 / 2017, the application of the principle there are differences in the implementation of the contract , the application of the system there is a significant difference, the application of the procedure there is no difference in the stages of completeness of the file and the settlement of credit or bad financing.